An Analysis of Cultural Contents in EFL Textbook: “Bahasa Inggris untuk SMP/MTs Kelas VII” - Muhammad Qozoli Wahid; Imam Qalyubi; Zaitun Qamariah (Journal on Education, 2023)
EFL textbooks are optimal resources for EFL teachers and students, providing essential materials for teaching and learning English. Cultural content in these textbooks is an important aspect that needs attention, because it plays an important role in shaping EFL students' attitudes and beliefs towards other cultures, especially in MTsN 1 school in Palangka Raya city. This study aims to find out (1) what aspects are included in the cultural content presented in the "Bahasa Inggris untuk SMP/MTs Kelas VII" textbook. then (2) What is the meaning of culture presented in the "Bahasa Inggris untuk SMP/MTs Kelas VII" textbook? Cultural content will be studied using descriptive and qualitative methods. The research subject is taken from the EFL Textbook:"Bahasa Inggris untuk SMP/MTs Kelas VII". The data sources used are the cultural content contained in the research books, observations and documents. The analysis in this study includes data collection, data presentation, and conclusion drawing. The research shows that the textbook "Bahasa Inggris untuk SMP/MTs Kelas VII" has an unbalanced ratio between the four aspects of culture (product, practice, perspective and society). The practical side dominates the content of the book, followed by the product side, the opinion side, and the social side. There are three types of cultural content in secondary school textbooks: source culture, target culture and international culture. Textbooks present more source culture than target culture and international culture.